Attitudes towards doping in participants of a popular long-distance road cycling event according to competing category - Zabala, M.; Freire, C.; Ramirez-Lechuga, J.; Morente-Sanchez, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The aim of this study was to know the attitudes towards to doping of non-professional cyclists taking account their competing category (Junior, U23, Elite, Master, Cycle-tourist, One-day License). Methods: A sample of 2022 amateur cyclists (40.95±9.42 years) who participated in a long-distance (205 km) Spanish road cyclist event called "Quebrantahuesos" (UCI Golden Bike), was divided into groups according to the competing category (30 Junior -G1-, 9 U23 -G2-, 32 elite -G3-, 546 Master -G4-, 1013 Cycle-tourist -G5-, 392 One-day License -G6-). Descriptive design was carried out by means of a validated questionnaire (Petroczi & Aidman, 2009) of 17 questions using a Likert scale from 1 (Strongly Disagree) to 6 (Strongly Agree) for different statements that supported the use of doping in sport. Mean value ± Standard Deviation was obtained for each item and Mann Whitney test for independent variables with Bonferroni post hoc was carried out. Results: The lowest overall score was observed for G6 (39.46±11.62) and G1 (40.07±11.61), and the highest was showed by G3 (49.06±14.10). For the mean score and overall score were observed significant differences between G6 vs G3, G4, G5 (p<0.001). For certain items there were significant differences between different groups: The risks related to doping are exaggerated (G3 vs G6, p<0.001); Athletes should not feel guilty about breaking the rules and taking performance enhancing drugs (G3 vs G6, p<0.001; G4 vs G6, p<0.002; G3 vs G5, p<0.003); Health problems related to rigorous training and injuries are just as bad as from doping (G3 vs G4 & G5 vs G6, p<0.001; G3 vs G5, p<0.002); The media blows the doping issue out of proportion (G3 vs G5 & G4 vs G5, p<0.001; G4 vs G6, p<0.002); Media should talk less about doping (G5 vs G1, G3, G4, G5. P<0.001). Just for one item ("Doping is not cheating since everyone does it") significant differences (P<0.001) were found between G1 (1.03±0.18) and G3 (1.84±1.35). Despite of not having significant differences, mean scores of G1, G2 and G3 were 2.36±0.69, 2.54±0.61 and 2.89±0. 83, increasing respectively. Discussion: This results contrast with others studies (Morente-Sánchez et al. 2011) which also used PEAS and where a sample of elite cyclists (Spanish cycling national team) showed a lower mean score (2.06±0,39). So, it seems that the higher age, the higher score. Due to the fact that overall scores are lower in Junior and U23 than elite, we consider that a psychosocial intervention since the earliest ages is needed to keep attitudinal levels.